Topsy‐turvy by the Belly Dancer. Issue 8 (15th July 2016) - Maud, Alberto; Qureshi, Ihtesham A.; Cruz‐Flores, Salvador; Rodriguez, Gustavo J.
Key Clinical Message: In our patient presenting with abdominal myoclonus, it is important to understand its pathophysiology. Various etiologies need to be taken into consideration before coming to a conclusion. The finding on Magnetic resonance imaging (MRI)‐Spine disclosing cervical lesion may just be an incidental finding. Abstract : In our patient presenting with abdominal myoclonus, it is important to understand its pathophysiology. Various etiologies need to be taken into consideration before coming to a conclusion. The finding on Magnetic resonance imaging (MRI)‐Spine disclosing cervical lesion may just be an incidental finding.